Malaysia's 14th general election the big issues - Kua, Kia Soong (Suara Initiatif Sdn Bhd, 2017)
Malaysia's 14th general election will no doubt be fought between a Barisan Nasional coalition that boasts its sixty years of "stable rule" and a Pakatan Rakyat coalition calling on the electorate to "save Malaysia" from the BN's kleptocracy. Malaysian voters will likely be treated to tirades about current scandals including 1MDB, as well as past scandals, now that the former Prime Minister Dr Mahathir has joined the Opposition. But what are the big issues of this election? This book, a compilation of the author's recent writings, discusses the important issues confronting Malaysian society today. If any sustainable democratic progress is to be made in this country, it is crucial that voters are informed and demand that candidates and their parties clarify their stand on these issues well before Election Day. Kua concludes with an alternative programme for Malaysia that is both inclusive and progressive -'Manifesto of the 99%' by The Left Coalition, to transcend the years of corruption, neo-liberal capitalism and lack of democracy. Failure to learn the lessons of the last sixty years of BN rule will condemn the country to a further dysfunctional future for the vast majority of Malaysians.